Antibacterial Activity of N-hexane and Diethyl Ether Fraction of Piper betle L. Leaf Against Staphylococcus aureus dan Escherichia coli Bacteria - Kunti Mulangsri, Dewi Andini; Ningrum, Ria Ayu; Imliyyah, Nafilatul (Indonesian Journal of Chemical Science, 2022)
Escherichia coli and Staphylococcus aureus bacteria are still cause of superficial and systemic infections. Fractionation of green betel leaf extract was carried out to obtain simpler compounds than the crude extract. The purpose of this study was to determine the antibacterial activity of the n-hexane fraction and the diethyl ether fraction of green betel leaf against Escherichia coli and Staphylococcus aureus. The extract of green betel leaf was fractionated with n-hexane and diethyl ether. The n-hexane fraction (HF) and diethyl ether fraction (DF) were tested for antibacterial activity using the disc diffusion method and the concentrations used were 0.5; 1; 1.5; 2; and 2.5 mg/disc. Chloramphenicol paper disc 30 µg/disk as a positive control and DMSO as a negative control. Data analysis was carried out descriptively by observing the inhibition zone around the paper disc which indicated the presence of antibacterial activity. The inhibition zone has measured the diameter of the inhibition area. The test results showed that there was antibacterial activity in the HF and DF of green betel leaf against Escherichia coli and Staphylococcus aureus bacteria, indicated by the presence of an inhibitory zone around the paper disc at all concentrations. The average diameter of the inhibition area produced against Escherichia coli and Staphylococcus aureus were 10.89–12.58 mm and 7.28-11.93 mm for green betel of HF and6.51–11.89 mm and 8.43–15.18 mm for green betel of DF, respectively